Characterization of curcumin-loaded nano thermo-sensitive hydrogel - Ikhsanudin Azis; Saifullah S Teuku Nanda; Zai Khadijah; Ari S Bambang (BIO Web of Conferences)
Breast cancer is one of the most common cancers affecting women. Breast cancer therapy is one of the targets of the Sustainable Development Goals (SDGs), namely reducing death rates and ensuring that people receive safe and quality medicines. This research aims to characterize thermosensitive nano hydrogel preparations with curcumin as a model drug based on the characteristics of the preparation. Thermosensitive nano hydrogels were formulated with various concentrations of curcumin, namely formulations F1 (10 mg/L), F2 (20 mg/L%), and F3 (40 mg/L). The results showed that the particle size in F I was 472 ± 2.50 nm; F II 423 ± 3.02 nm and F III 455 ± 4.81 nm statistically show a p value <0.05. Data from the zeta potential test results show FI -7.95 ± 1.00 mV, F II -12.47 ± 0.91 mV, and F III -13.33 ± 0.64 mV, with p-value < 0.05 and pH testing shows that F I is 4.73 ± 0.01; FII 4.76 ± 0.01; F III 4.83 ± 0.02, with p-value <0.05. Meanwhile, the stability test of the flask-sensitive hydrogel preparation showed a curcumin F I content of 97.6 ± 0.02%; F II 98.3 ± 0.015%; F III 98.9 ± 0.01%, with p-value <0.05. For the test data, the sol-gel transition time F I was 114 ± 2.08 seconds; F II 112 ± 4.58 seconds; III 154 ± 5.51 seconds with p-value <0.05. F I viscosity data 3,335.98 ± 374.11 cps; F II 2,734.62 ± 428.33 cps; F III 1,923.14 ± 149.86 cps with p value > 0.05. This study concluded that the concentration of poloxamer-407 could reduce particle size, polydispersibility index, zeta potential, and viscosity.